Paternal pre-conceptional nutrition programs breast cancer risk in rat female offspring: opposing effects of animal- and plant- based high fat diets - Fontelles, Camile Castilho (2016)
Breast cancer is a persistent public health problem. Interesting hypothesis suggests that its risk can be modulated in early life periods, a phenomenon known as fetal programming. In this context, most fetal programming studies focus on maternal influence, due to the greater interaction between mother and fetus in both fetal and lactation periods. However, recent studies show that paternal preconception diet has also a major role in the offspring\'s susceptibility to metabolic chronic non-communicable diseases. Therefore, this direct doctoral project aimed to assess whether the paternal consumption of different high fat diets during the development period of the reproductive system of male rats increased the susceptibility of female offspring to mammary carcinogenesis. In addition we sought to evaluate which mechanisms could be involved in this process. We used male rats of the Sprague-Dawley strain (n = 20/group) that consumed high fat diet with 60% of calories from lipids from lard (LB group) or corn oil (CB group), or AIN-93G control diet (CO group) for nine weeks, during development and sexual maturation periods. These rats were mated with females who consumed only commercial diet in 1:1 ratio. Their 50 days old offspring were subjected to mammary carcinogenesis model using 7,12-dimethylbenz[a]anthracene (50mg/kg). Paternal consumption of high fat diet of animal or plant source had opposite effects, with the paternal consumption of diet with high content of saturated fatty acids (LB) increasing and consumption of diet with high content of n-6 polyunsaturated fatty acids (CB) reducing the risk of breast cancer development in female offspring. These effects were due to changes in the expression of 89 miRNAs in the father\'s sperm and 23 miRNAs in the offspring\'s mammary gland, with overlapping of three miRNAs (miR-1897-5p, miR- 219-1-3p and miR-376a #) that were altered in both tissues. Additionally, female offspring of males fed diets with high content of saturated fatty acids showed less differentiation of the mammary gland, higher levels of cell proliferation, lower levels of apoptosis and altered expression of keys proteins that regulate important cellular functions, such as epithelial to mesenchymal transition. Finally, these females had also altered lipid profile of the fat pad similar to their male parent as well as epigenetic changes that may be related to the etiology of breast cancer. Thus, we conclude that the high-fat preconception paternal diet programmed the susceptibility of female offspring to mammary carcinogenesis, but this effect was dependent on the type of fatty acid consumed and the observed effects possibly results from changes in miRNA expression profile.